2006
DOI: 10.1364/ao.45.002766
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz birefringence and attenuation properties of wood and paper

Abstract: The far-infrared properties of spruce wood are examined with a terahertz time-domain spectrometer. The solid wood is shown to exhibit both birefringence and diattenuation. The birefringence properties are sufficient for construction of a quarter-wave plate operating at 0.36 THz, and a half-wave plate operating at 0.71 THz. The origin of the birefringence is attributed to preferential fiber orientation within the wood. Similar birefringence is observed in lens paper in which the fibers are preferentially orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
78
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 12 publications
3
78
0
2
Order By: Relevance
“…Furthermore, polymers reinforced by aligned glass fibers were found to be birefringent [3,4,64] due to the embedded fibers representing sub-wavelength structures along one direction with regard to the relatively large THz wavelengths in the 100 μm range. Moreover, THz birefringence was observed for textiles [53], a Yucca plant leaf [2], different types of wood [65,66], but also for paper [53,65,67], which exhibits a preferential orientation of the cellulose fibers due to the production process. In particular for wood it was demonstrated that the observed birefringence exhibits contributions not only from form birefringence but also from intrinsic birefringence due to the crystalline structure and microfibril angles of the wood fibers [66].…”
Section: Birefringence At Thz Frequenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, polymers reinforced by aligned glass fibers were found to be birefringent [3,4,64] due to the embedded fibers representing sub-wavelength structures along one direction with regard to the relatively large THz wavelengths in the 100 μm range. Moreover, THz birefringence was observed for textiles [53], a Yucca plant leaf [2], different types of wood [65,66], but also for paper [53,65,67], which exhibits a preferential orientation of the cellulose fibers due to the production process. In particular for wood it was demonstrated that the observed birefringence exhibits contributions not only from form birefringence but also from intrinsic birefringence due to the crystalline structure and microfibril angles of the wood fibers [66].…”
Section: Birefringence At Thz Frequenciesmentioning
confidence: 99%
“…On the one hand, materials can be characterized with regard to their use for THz quasi-optical polarization devices. As an example, quartz plates [68], metamaterials [56,58,69], liquid crystals [70], but also paper [61] and wood [65] have been proposed and employed for the fabrication of monochromatic and, in the case of quartz, also achromatic THz wave plates. Moreover, especially when samples are opaque for visible or NIR light, valuable information about anisotropic material properties can be obtained, which are hard to get with other non-destructive methods.…”
Section: Birefringence At Thz Frequenciesmentioning
confidence: 99%
“…Another proposal to determine both refractive indices and optical axis in a single measure is developed in [7], where the terahertz spectrometer employs circularly polarized terahertz waves and a polarization-sensitive detector that measures both components of the electric field simultaneously. However, this method is not applicable with a standard terahertz spectrometer.In this Letter, we propose a technique for measuring the average refractive indices of birefringent materials in a single measurement and a method for obtaining the optical axis orientation in materials with constant refractive index in the terahertz range, such as various plastics, paper, or wood [3,6]. The method relies on the information obtained from the interference generated by the temporal pulses and echoes in the frequency domain.…”
mentioning
confidence: 99%
“…However, it requires at least four measurements, which can be both slow and cumbersome. A faster way to obtain average refractive indices is by measuring the delay between the peaks of the main pulses and their respective echoes in the temporal domain [6]. This method can only be applied when the delays between pulses and echoes are long enough to distinguish them.…”
mentioning
confidence: 99%
See 1 more Smart Citation